A new I3O93− group constructed from IO3− and IO55− anion units in Cs3[Ga2O(I3O9)(IO3)4(HIO3)]. Issue 1 (23rd November 2021) - Wang, Dandan; Jiang, Xiaoqing; Gong, Pifu; Zhang, Xinyuan; Lin, Zheshuai; Hu, Zhanggui; Wu, Yicheng
Abstract : Cs3 [Ga2 O(I3 O9 )(IO3 )4 (HIO3 )] with a novel I3 O9 3− fundamental building block (FBB) constituted by two IO3 and one IO5 polyhedra exhibited a wide band gap. Abstract : An alkali metal gallium iodate, Cs3 [Ga2 O(I3 O9 )(IO3 )4 (HIO3 )] (CGIO ), was synthesized by the traditional hydrothermal method. Interestingly, CGIO revealed a novel I3 O9 3− fundamental building block (FBB) constituted by two IO3 tetrahedrons and one IO5 polyhedron through sharing O atoms. The new I3 O9 3− trimer forms a 0D [Ga2 O(I3 O9 )(IO3 )4 (HIO3 )] 3− anion cluster together with the [Ga2 O11 ] 16− dimer and isolated IO3 − units. The UV-vis-NIR diffuse reflectance spectrum of CGIO shows a wide bandgap of 4.05 eV, and the thermal stability could reach above 400 °C. First-principles calculations explicated that the optical properties of CGIO mainly originated from the iodate anion units with a calculated birefringence of 0.04 at 1064 nm.